Med zgodovino in biografijo - Knop, Seta (Primerjalna književnost, 2015)
The paper discusses different narrative techniques used in the historical works by Danilo Kiš, Yury Trifonov and Lado Kralj; starting from the autopoetics of the writers themselves it thematizes the way how to unite fiction and truth and the role of (pseudo)documentary sources in the elusive relation between them.
Keywords: dokumentarnost; fikcija in resničnost; Kiš, Danilo; književnost in zgodovina; Kralj, Lado; primerjalne študije; ruska književnost; ruska revolucija; slovenska književnost; srbska književnost; Trifonov, Jurij; zgodovinski romani